2016
DOI: 10.1002/lsm.22546
|View full text |Cite
|
Sign up to set email alerts
|

Non‐insulated smooth motion, micro‐needles RF fractional treatment for wrinkle reduction and lifting of the lower face: International study

Abstract: This multicenter study showed significant wrinkle reduction, skin tightening, and lifting of the mid and lower face with the noninsulated fractional RF microneedling system. Lasers Surg. Med. 48:727-733, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 17 publications
(19 reference statements)
5
61
0
2
Order By: Relevance
“…Caesarea, Israel) for tightening and acne scar treatments ( Figures 6 and 7) [22][23][24][25]. The system platform (1MHZ) incorporates six independent phase controlled RF generators that allow the RF microneedles to induce skin remodeling through controlled dermal coagulation.…”
Section: Dermatologic Surgery and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Caesarea, Israel) for tightening and acne scar treatments ( Figures 6 and 7) [22][23][24][25]. The system platform (1MHZ) incorporates six independent phase controlled RF generators that allow the RF microneedles to induce skin remodeling through controlled dermal coagulation.…”
Section: Dermatologic Surgery and Proceduresmentioning
confidence: 99%
“…In addition, RF emission through the length of the needle provides for shorter treatment times and a coagulation effect that eliminate micro-bleeding and improve the patient experience [22][23][24][25][26]. Digital control of the needle penetration depth with automatic motorized insertion improves the patient experience by reducing discomfort and side effects [22][23][24][25][26].…”
Section: Rf Microneedle Treatmentsmentioning
confidence: 99%
“…It has been documented that treatment of the skin with RF microneedling has a rejuvenating effect . Dermal remodeling after RF microneedling was shown to produce new collagen, elastin, and hyaluronic acid .…”
Section: Discussionmentioning
confidence: 99%
“…This cosmetic procedure is minimally invasive and utilizes fine needles to puncture the skin creating micro‐wounds which induces release of growth factors and induction of collagen and elastin production . Recently, Gold and colleagues investigated using radiofrequency (RF) microneedling in treating wrinkles and skin laxity of the mid and lower face . The investigators evaluated EndyMed's treatment platform with the Intensif ™ applicator (EndyMed, Caesarea, Israel).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with Microneedles headed to slow and continued development in the skin's wrinkles that was higher to Botox injection [68]. Gold et al, (2016) reported the special effects of microneedles fractional radio-frequency management on dermal rejuvenation and testified in terms of wrinkle lessening, skin constriction, and lifting of the middle and lower face in most of patients, without any adversative effects detected during study [69].…”
Section: Microneedlesmentioning
confidence: 98%